Preserved ratio impaired spirometry with or without restrictive spirometric abnormality - Shinichiro Miura; Hiroshi Iwamoto; Keitaro Omori; Kakuhiro Yamaguchi; Shinjiro Sakamoto; Yasushi Horimasu; Takeshi Masuda; Shintaro Miyamoto; Taku Nakashima; Kazunori Fujitaka; Hironobu Hamada; Akihito Yokoyama; et al. (Scientific Reports, 2023)
Abstract Preserved ratio impaired spirometry (PRISm) is defined by reduced FEV1 with a preserved FEV1/FVC ratio; some individuals with PRISm can also have restrictive ventilatory abnormality. The aim of this study was to clarify clinical features of restrictive and non-restrictive PRISm. In total, 11,246 participants (mean, 49.1 years; range, 35–65 years) from five healthcare centres were included in this study. We evaluated baseline characteristics of participants with restrictive PRISm (FEV1/FVC ≥ 0.7, FEV1 < 80% and FVC < 80%) and non-restrictive PRISm (FEV1/FVC ≥ 0.7, FEV1 < 80% and FVC ≥ 80%), and airflow obstruction (FEV1/FVC < 0.7). We examined the longitudinal risk of developing airflow obstruction by comparing spirometry results at baseline and 5 years post-baseline among 2141 participants. Multivariate analysis demonstrated that a history of asthma or smoking could constitute an independent risk factor for non-restrictive PRISm, and that non-restrictive PRISm was independently associated with the risk of developing airflow obstruction. In contrast, female sex, advanced age, and high BMI, but not history of asthma or smoking, were risk factors for restrictive PRISm. Restrictive PRISm was not associated with the development of airflow obstruction. In conclusion, our results indicate that PRISm can be categorized according to the presence or absence of restrictive abnormality. Non-restrictive PRISm, which does not meet the conventional criteria of obstructive and restrictive ventilatory abnormalities, may be a precursor of chronic obstructive pulmonary disease and merits increased monitoring.